Совместные текущие разработки и исследования ХНУРЭ АО НАН Украины в области точного ГНСС-позиционирования - Жалило, А. А.; Желанов, А. А.; Шелковенков, Д. А.; Дицкий, И. Е.; Бессонов, Е. А. (ХНУРЭ, 2011)
The main results of joint creation and researches of new effective methods and algorithms of GNSS data processing for high precision positioning by specialists of KhNURE and MAO NASU in 2010-2011 are presented. There are briefly described the directions of R&D activities, carried out projects, formulated new approach and achievements in dual-/single-frequency static/kinematic positioning developments.
Keywords: GPS-группа; ГНСС-технологии навигации; точное позиционирование